The effects of GLP-1 based therapies on postprandial haemodynamics: Two randomised, placebo-controlled trials in overweight type 2 diabetes patients. (February 2017) - Smits, Mark M.; Tonneijck, Lennart; Muskiet, Marcel H.A.; Hoekstra, Trynke; Kramer, Mark H.H.; Diamant, Michaela; van Raalte, Daniël H.
Abstract: Aims: To assess the effects of glucagon-like peptide (GLP)-1 receptor agonists and dipeptidyl peptidase (DPP)-4 inhibitors on postprandial haemodynamics. Methods: 57 patients with type 2 diabetes (mean ± SD age 62.8 ± 6.9 years; BMI 31.8 ± 4.1 kg/m 2 ; HbA1c 7.3 ± 0.6%) were included in an acute (exenatide- or placebo-infusion) and 12-week (liraglutide, sitagliptin or placebo) randomised, placebo-controlled, double-blind trial. Systemic haemodynamics (oscillometric technique and finger photoplethysmography), vascular stiffness (tonometry), and sympathetic nervous system (SNS)-activity (heart rate variability) were determined in the fasting state and following a standardised mixed meal. Results: In both studies, postprandial blood pressure (BP) decreased during placebo-intervention. Compared with placebo, acute exenatide-infusion increased postprandial diastolic BP (6.7 [95%-confidence interval 3.6–9.9] mmHg, p  < 0.001) and vascular resistance (683.6 [438.5–928.8] dyn*s/cm 5 /1.73 m 2, p  < 0.001), while cardiac index decreased (0.6 [0.40.8] L/min/1.73 m 2 ; p  < 0.001). Systolic BP, augmentation index and SNS-activity were unaffected. Twelve-week liraglutide-treatment did not affect postprandial haemodynamics, while sitagliptin decreased diastolic BP (3.5 [0.0–6.9] mmHg; p  = 0.050), vascular resistance (309.9 [66.6–553.1] dyn*s/cm 5 /1.73 m 2 ; p  = 0.013) and cardiac index (0.3 [0.0–0.6] L/min/1.73 m 2 ; p  = 0.040), compared with placebo. Neither liraglutide nor sitagliptin affected SNS-activity or augmentation index. All treatments significantly lowered postprandial glucose levels. Conclusions: Acute exenatide-infusion prevented the meal-induced decline in diastolic BP, although prolonged liraglutide intervention did not affect postprandial haemodynamics. The meal-induced drop in BP was augmented during sitagliptin-treatment.